Vibration analysis of FGM plates in thermal environment resting on elastic foundation using ES-MITC3 element and prediction of ANN. (April 2021) - Tran, Trung Thanh; Nguyen, Phu-Cuong; Pham, Quoc-Hoa
Abstract: In this article, some numerical results from the free vibration analysis of functionally graded material (FGM) plates resting on the elastic foundation (EF) in the thermal environment are presented. An ES-FEM combining with the MITC3 is used to improve the accuracy as well as eliminate the shear locking phenomena for the classical triangular element. The EF is modeled from the Winkler-Pasternak foundation with stiffness two-parameter. Numerical examples are compared with published works to prove the reliability and accuracy of the proposed method. The effects of volume fraction index ( n ), temperature ( T ), and two-parameter of the EF on the free vibration of FGM plates are also investigated. Furthermore, an artificial neural network (ANN) is trained to predict exactly the fundamental frequency of FGM plates. Highlights: Extend the ES-MITC3 element for the free vibration analyses of FGM plates resting on the elastic foundation in the thermal environment. Investigate the influences of geometric parameters, material properties, and foundation stiffness on the free vibration of FGP plates. Set up an ANN to predict the fundamental frequency of FGP plates resting on the elastic foundation in the thermal environment with four input-data.